Rich internet applications (RIA): the plurality of contents - Lara-Navarra, Pablo; Maniega-Legarda, David (Anuario ThinkEPI, 2010)
The article outlines the main features of the RIA technologies (Rich internet applications). The contents packaged with RIA technology are updated independently and, among other benefits, ensure interoperability between platforms and formats, so they can generate multi-platform contents.
Keywords: Technologie; RIA; Rich Internet Applications